2021
DOI: 10.1093/ije/dyab079
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined effects of individual and neighbourhood socio-economic disadvantage on health-related lifestyle risk factors: a multilevel analysis

Abstract: Background Socio-economic disadvantage at both individual and neighbourhood levels has been found to be associated with single lifestyle risk factors. However, it is unknown to what extent their combined effects contribute to a broad lifestyle profile. We aimed to (i) investigate the associations of individual socio-economic disadvantage (ISED) and neighbourhood socio-economic disadvantage (NSED) in relation to an extended score of health-related lifestyle risk factors (lifestyle risk index);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…Several epidemiological studies have shown that differences in socio-economic and demographic characteristics carry a considerable impact on lifestyle risk factors [7]. For instance, individuals from low socio-economic status tend to have unhealthier lifestyle, such as unhealthy diets and decreased time spent on physical activity [8]. Moreover, differences within individual socio-economic status (SES) exist.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several epidemiological studies have shown that differences in socio-economic and demographic characteristics carry a considerable impact on lifestyle risk factors [7]. For instance, individuals from low socio-economic status tend to have unhealthier lifestyle, such as unhealthy diets and decreased time spent on physical activity [8]. Moreover, differences within individual socio-economic status (SES) exist.…”
Section: Introductionmentioning
confidence: 99%
“…Poor health and diet quality are associated with individuals pertaining to a low socio-economic status (SES), as compared to those from middle or high SES [7,8]. Other socio-demographic characteristics can be associated with diet quality, such as the place of birth, education background, race/ethnicity and family aspects (such as the number of kids and their age) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that we observed direct effects of education on obesity status, as well as of income, diet quality, and smoking on type 2 diabetes. A cautious interpretation is warranted, as it cannot be excluded that the observed direct effects are in fact due to other, but unobserved, existing mediators or confounders, such as neighborhood deprivation (distal environmental factors) and chronic inflammation (proximal clinical biomarkers) (Dekker et al, 2020;Kivimäki et al, 2018;Zhu et al, 2021).…”
Section: Table 1 Baseline Characteristics By Diabetes Statusmentioning
confidence: 99%
“…More specifically, obesity and abnormal blood lipids are largely attributed to unhealthy lifestyle behaviors, whereas all are strongly influenced by socioeconomic status. These factors, in turn, collectively form several hypothesized intersecting pathways that lead to the eventual development of type 2 diabetes (Duan et al, 2021;Foster et al, 2018;Maty et al, 2005;Vinke et al, 2020;Zhu et al, 2021). Socioeconomic status is thus considered the overarching upstream determinant of type 2 diabetes for its significant effects on proximal (or downstream) risk factors.…”
Section: Introductionmentioning
confidence: 99%